Introduction to psychology active learning through modules - Coon, Dennis; Mitterer, John O. (Wadsworth, Cengage Learning, 2012)
Global Psychology in Active Learning Modules, International Edition, the best-selling text by renowned author and educator Dennis Coon and John O. Mitterer, combines the highly effective SQ4R (Survey, Question, Read, Recite, Reflect, Review) active learning system, an engaging style and appealing visuals, and detailed coverage of core topics and cutting-edge research in one remarkable, comprehensive text. Fully updated and reorganized, this edition includes new and revised content, extensive special features, and learning tools integrated throughout the text. While the text provides a thorough introduction to the study of psychology, its modular design and emphasis on how psychology relates to everyday life make it easy for students to explore, enjoy, and ultimately master a wide variety of topics.